Civil War II. Amazing Spider-Man - Gage, Christos; Foreman, Travel (2016)
"There's a new inhuman with the ability to predict the future, and as Earth's heroes grapple with their feelings about his very existence, there's one fact on which almost everyone can agree: this Ulysses bears great power, and has a tremendous responsibility to use it safely. Peter Parker knows a thing or two about that, so who better to serve as a mentor? But when that ol' Parker luck strikes, Ulysses predicts someone close to Spidey is about to turn traitor. Could it be that one of his oldest foes is about to return? As friends turn against friends across the Marvel Universe, Spider-Man is no exception--but with whom will he clash?"--Page 4 of cover.
"Originally published in single magazine form as Civil war II: Amazing Spider-man #1-4 and Amazing Spider-man #7-8."
Chiefly illustrations.
T+.
Keywords: Spider-Man -- (Fictitious character) -- Comic books, strips, etc; Spider-Man -- (Fictitious character); Superheroes -- Comic books, strips, etc; Civil war -- Comic books, strips, etc; Prophecies -- Comic books, strips, etc; Traitors -- Comic books, strips, etc; Forecasting -- Comic books, strips, etc; Imaginary wars and battles -- Comic books, strips, etc; Civil war; Forecasting; Imaginary wars and battles; Prophecies; Superheroes; Traitors; Imaginary wars and battles -- Comic books, strips, etc; Graphic novels; Prophecies -- Comic books, strips, etc; Superhero comics; Science fiction comics; Superhero comics; Science fiction comics; Graphic novels; Comic books, strips, etc; Graphic novels; Graphic novels, Juvenile; Superhero comic books, strips, etc; Science fiction comics; Superhero comics